SMART MAPPING BERBASIS QGIS: PEMETAAN DIGITAL DAERAH RAWAN BENCANA MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Teguh Setiadi; Febriyanti Darnis (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
Batang Regency features diverse geographical characteristics, including coastal areas, lowlands, and mountains, which make it vulnerable to various natural disasters such as floods, landslides, and volcanic eruptions. The increasing activity of sand and stone mining along rivers has further exacerbated environmental degradation, heightening the risk of such disasters. To address this issue, a system is needed to help the local government accurately classify disaster-prone areas. A Geographic Information System (GIS) for disaster risk mapping serves as an effective solution to identify and visualise vulnerable locations across Batang Regency. This system supports disaster prevention, response, and targeted aid distribution. With public access to the system, it also promotes data transparency, strengthens community trust in the local government, and raises public awareness of potential disaster threats in their surroundings.